Acute lymphoblastic leukemia: Primary bone manifestation with hypercalcemia in a child - Oliveira, Cristiano C. [UNESP] (2017)
Primary bone manifestation associated with hypercalcemia is an infrequent presentation of acute lymphoblastic leukemia (ALL) in children. An 8-year-old girl was admitted with bone and abdomen pain, vomiting, fever, headache, anemia, elevated serum calcium and normal parathyroid hormone levels. Bone radiographs: osteolytic lesions. Bone marrow biopsy showed an infiltration by ALL with immunohistochemical positivity for CD45, CD20, CD79a, TdT and CD10, clinically characterized by hypercalcemia, multifocal osteolytic lesions and single cytopenia. Bone marrow biopsy was a relevant aid in establishing the diagnosis of multifocal osteolytic lesions, associated with hypercalcemia.